2014
DOI: 10.1007/s12288-014-0462-5
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on Burden of Hepatitis C, Hepatitis B, HIV and Syphilis in Multi-Transfused Thalassemia Major Patients Reporting to a Government Hospital of Central India

Abstract: Need for frequent blood transfusions exposes thalassemia major patients to risk of transfusion-transmitted infections (TTIs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…At the next rates are HBV with four patients (0.68%) and HIV positive with 0%. In some research, such as that of Yaghobi (HCV: 18.86%), Ansari (HCV: 13.1%), Manisha (HCV: 18%), and Gene (HCV: 25%), the prevalence of HCV serology was higher than in our study ( 12 – 14 ). On the other hand, in research performed by Ataie (HCV: 18%), Calderon (HCV: 1.7), Vidga (HCV: 2%), Chakrabarti (HCV: 2%), and Aza (HCV: 7.8%), the spread was lower than in our study ( 15 – 18 ).…”
Section: Discussioncontrasting
confidence: 74%
“…At the next rates are HBV with four patients (0.68%) and HIV positive with 0%. In some research, such as that of Yaghobi (HCV: 18.86%), Ansari (HCV: 13.1%), Manisha (HCV: 18%), and Gene (HCV: 25%), the prevalence of HCV serology was higher than in our study ( 12 – 14 ). On the other hand, in research performed by Ataie (HCV: 18%), Calderon (HCV: 1.7), Vidga (HCV: 2%), Chakrabarti (HCV: 2%), and Aza (HCV: 7.8%), the spread was lower than in our study ( 15 – 18 ).…”
Section: Discussioncontrasting
confidence: 74%
“…15 In India, the prevalence of HCV in thalassemic patients as reported by recent epidemiological studies varies from 18.2% to 25%. [16][17][18][19] Though observational studies demonstrated high SVR rates in real life cohorts of Indian patients with SOF-based treatment, there was no well-established Indian guideline for treatment of HCV with DAA in thalassemic patients. 6,20 Hence, we carried out this study to evaluate efficacy and safety of SOF-based regimen in this special population.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate other studies [ 28 , 32 ] that also found no positive cases for HIV in thalassemic patients. Nevertheless, an Indian study found that the seroprevalence of HIV was about 1.5% [ 34 ].…”
Section: Discussionmentioning
confidence: 99%